Foreign tourist trips of Polish residents in the context of the COVID-19 pandemic - Matczak, Andrzej; Szymańska, Daniela (Bulletin of Geography. Socio-economic Series, 2025)
The article addresses the impact of the COVID-19 pandemic on the tourist behaviour of Polish residents traveling abroad. Based on publicly available data for 2018–2023 from mass surveys conducted by the Statistics Poland (GUS), it was found that the COVID-19 pandemic in reduced the number of Poles traveling abroad for tourist purposes 2020–2021 by more than half and partially changed their tourist behaviour in terms of the frequency, purposes and season of traveling abroad; the choice of accommodation facilities and means of transport; travel expenses: and destinations of foreign trips compared to the pre-pandemic period (2018–2019). The changes in tourist behaviour of Polish residents caused by the COVID-19 pandemic were largely similar to the changes observed in the societies of many European countries. The change in Poles' tourist behaviour resulting from the pandemic turned out to be temporary. In 2022–2023, the numbers of foreign-destination tourist trips recovered, and there was a return to and continuation of the trends in tourist behaviour of Poles traveling abroad that were observed in the period preceding the COVID-19 pandemic.